Address to AIDS donors conference, 5 December 1988, Barbados Hilton - Rainford, Roderick G. ([Caricom Secretariat] GeorgetownGY, 1988)
Puts forward the view that our response to the challenge for aids education and sensitization needs to be integrated creatively into our programmes at the global, regional and national levels. States that we must continue designing appropriate action and interventions to combat the spread of the virus and to pursue the mobilisation of resources to give practical effect to the programmes that are designed.